Coastal sea levels and wind-waves in the Mediterranean Sea since 1950 from a high-resolution ocean reanalysis - Toomey, Tim; Amores, Angel; Marcos, Marta; Orfila, Alejandro (Frontiers in Marine Science, 2022)
In the Mediterranean Sea, coastal extreme sea levels are mainly caused by storm surges driven by atmospheric pressure and surface winds from extratropical cyclones. In addition, wind-waves generated by the same atmospheric perturbations may also contribute to coastal extremes through wave setup (temporal rise above the mean sea level due to dissipation and breaking of waves in shallow waters close to the shore). This study investigates the spatial and temporal variability of coastal extreme sea levels in the Mediterranean basin, using a new ocean hindcast generated with a coupled hydrodynamic-wave model that simulates storm surges and wind-waves. The numerical simulation covers the period 1950-2021 with high temporal sampling (1h) and at unprecedented spatial resolution that reaches 200 m along the coastlines. Coastal storm surges and wave heights are validated with available observations (tide gauges, waves buoys and satellites). Comparison against tide gauges shows an average RMSE of 7.5 cm (7.7m for extreme events) and mean linear correlation of 0.64 for the whole period. Similarly, comparison of simulated and observed significant wave height shows good agreement, with RMSE lower than 0.25 m and a coefficient correlation as high as 0.95. The results confirm that coastal extreme sea levels are more likely to be located in regions with wide continental shelves favouring the wind contribution to storm surges along with shallow waters that favour wave setup induced by depth-breaking. The contribution of waves to coastal extreme sea levels has been quantified, using the hindcast in combination with an uncoupled simulation and has been shown to be significant, with an assessed wave setup spatial footprint at regional scale and values reaching up to 120% of observed maximum sea levels.